2020
DOI: 10.1186/s12909-020-02127-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of profession-role exchange in an interprofessional student team-based community health service-learning experience

Abstract: Background: During interprofessional clinical practice, compared to understanding of one's own professional role and function, it might be more difficult to clarify the roles and contributions of the other health-care team members because of the inter-professional barrier. In order to provide students the opportunity for real experience with other professions in team environments and enhance their perceptions of other professions' roles, this study developed a comprehensive and multi-dimension extracurricular … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…Of these, some have even shown to enhance students' awareness and perspectives of humanism in medicine (9,28). While studies have shown that professional-role exchange can better initiate students to the practice of interprofessional collaboration and enhance the awareness of medical students' role (29,30). In accordance with our ndings, research on IPE shows a positive impact on the cooperation between the medical and nursing professionals (30).…”
Section: Overall Bene Tssupporting
confidence: 72%
“…Of these, some have even shown to enhance students' awareness and perspectives of humanism in medicine (9,28). While studies have shown that professional-role exchange can better initiate students to the practice of interprofessional collaboration and enhance the awareness of medical students' role (29,30). In accordance with our ndings, research on IPE shows a positive impact on the cooperation between the medical and nursing professionals (30).…”
Section: Overall Bene Tssupporting
confidence: 72%
“…As a critical component of modern patient-centered healthcare practices, the interprofessional team–based model of care in which multiple healthcare professionals including physicians, nurses and pharmacists, etc. work together has been associated with enhanced patient satisfaction and better quality in patient care ( 108 , 109 ). It has been well-accepted that interprofessional team training should commence at the undergraduate level and continue into clinical practice ( 91 ).…”
Section: Resultsmentioning
confidence: 99%
“…More broadly, several studies show that many residents and medical students can have preconceived assumptions or stereotypes of other professions, particularly in contrast to their own professional identity, which inhibits teamwork as well as the IP-CLE. [28][29][30] The literature supports the effectiveness of interprofessional education efforts to moderate these inappropriate assumptions 28,29 and, in particular, supports a focus on deeper understanding of each other's roles as a stimulus for interprofessional collaboration, 31,32 the aforementioned REFLECT program to be interprofessional. Other institutions wishing to overcome barriers to IP QIPS may consider that an increased emphasis on IP education may be integral to QIPS training.…”
Section: Cultural Issues Influence the Interprofessional Clementioning
confidence: 95%